1996
DOI: 10.1063/1.116993
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated microcrystalline silicon germanium: A bottom cell material for amorphous silicon-based tandem solar cells

Abstract: We have developed hydrogenated microcrystalline silicon germanium, which exhibits a red-shifted absorption spectrum relative to hydrogenated microcrystalline silicon, as a candidate material for the bottom cell of amorphous silicon-based tandem solar cells. Optical absorption, x-ray diffraction, and Raman scattering spectra are presented in addition to optoelectronic properties and light-induced changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 5 publications
4
42
0
Order By: Relevance
“…38,39) Initially, aSiGe:H was adopted for bottom cell materials; however, this material shows severe photoinduced degradation. 40) Recently, c-Si:H or c-SiGe:H has been proposed as promising candidates for bottom cell materials, [41][42][43] because they do not exhibit photoinduced degradation. In this proposal, a high rate growth of these materials is crucial for low-cost fabrication of tandem solar cells, since c-Si:H as well as c-SiGe:H essentially has an indirect optical-transition nature.…”
Section: Solar Cell Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39) Initially, aSiGe:H was adopted for bottom cell materials; however, this material shows severe photoinduced degradation. 40) Recently, c-Si:H or c-SiGe:H has been proposed as promising candidates for bottom cell materials, [41][42][43] because they do not exhibit photoinduced degradation. In this proposal, a high rate growth of these materials is crucial for low-cost fabrication of tandem solar cells, since c-Si:H as well as c-SiGe:H essentially has an indirect optical-transition nature.…”
Section: Solar Cell Applicationsmentioning
confidence: 99%
“…Several monolayers of amorphous silicon are deposited and these layers are exposed to hydrogen atoms produced in the hydrogen plasma. These procedures are repeated alternately for [40][41][42][43][44][45][46][47][48][49][50] times to obtain the suitable thickness for the evaluation of film structure. The absence of marked reduction of the film thickness during the hydrogen-plasma treatment is difficult to explain by the etching model and hence the chemicalannealing model has been proposed.…”
Section: Growth Models For C-si:hmentioning
confidence: 99%
“…When applying our optimized substrates with low reflection and low absorption losses, the even higher J sc up to 25-27 mA/cm 2 can be reached for mc-Si 0 . 9 [12]. The detail of the optimization of single junction devices will be reported elsewhere.…”
Section: Single Junction Devicesmentioning
confidence: 99%
“…Here, we propose an alternative approach, i.e., the absorption enhancement of the bottom cell by alloying with germanium. Hydrogenated microcrystalline Si 1-x Ge x (mc-Si 1-x Ge x :H) alloys have been developed as a narrower variable band gap absorber for multi-junction solar cell application [9][10][11][12]. Recently, we have fabricated p-i-n single junction solar cells incorporating mc-Si 1-enhancement in the infrared response with excellent performance stability under prolonged light soaking [12].…”
Section: Introductionmentioning
confidence: 99%
“…1-7 µc-SiGe:H features a higher absorption coefficient than microcrystalline silicon (µc-Si:H) throughout the solar spectrum, [4][5][6][7][8][9] whereas the optoelectronic quality of the µc-Si 1−x Ge x :H films is usually not satisfactory due to the increased defect density with Ge incorporation. [10][11][12][13] It has been reported that the electronic conductivity in the dark and under illumination depends strongly on the structural composition of µc-Si 1−x Ge x :H films.…”
Section: Introductionmentioning
confidence: 99%